Response - Peter P. Swire (Washington University Law Quarterly, 1999)
I recognize some of Lynn’s comments on my paper and do not recognize others. Let me take the three points in turn.
Keywords: Right of privacy; Financial services industry; Electronic surveillance; Phase 2 Plus (Company); Bank secrecy; Financial services